United Nations Conference on Trade and Development: Trade and Development Board official records, twenty-ninth session 10-27 September, 1984 - United Nations; United Nations (New York : United Nations, 1985)
The book contains the summary records of the meetings held by the board during its twenty-ninth session.
usc 20/02/2019
Loans
Keywords: Commercial policy; Economic development; Economic policy; Developing countries